2016
DOI: 10.1038/srep22146
|View full text |Cite
|
Sign up to set email alerts
|

In situ Proteomic Profiling of Curcumin Targets in HCT116 Colon Cancer Cell Line

Abstract: To date, the exact targets and mechanism of action of curcumin, a natural product with anti-inflammatory and anti-cancer properties, remain elusive. Here we synthesized a cell permeable curcumin probe (Cur-P) with an alkyne moiety, which can be tagged with biotin for affinity enrichment, or with a fluorescent dye for visualization of the direct-binding protein targets of curcumin in situ. iTRAQTM quantitative proteomics approach was applied to distinguish the specific binding targets from the non-specific ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 39 publications
1
59
0
1
Order By: Relevance
“…The Curcumin-probe (Curcumin-P) was readily synthesized by mono-alkylation of curcumin by propargyl bromide and its structure was verified by H-NMR, C-NMR and high resolution mass spectrometry [40]. …”
Section: Methodsmentioning
confidence: 99%
“…The Curcumin-probe (Curcumin-P) was readily synthesized by mono-alkylation of curcumin by propargyl bromide and its structure was verified by H-NMR, C-NMR and high resolution mass spectrometry [40]. …”
Section: Methodsmentioning
confidence: 99%
“…Curcumin is a versatile natural molecule that is possessing multitude of confirmed therapeutic activities but it is very safe and can be tolerated in high doses up to 10g/day [19, 20]. Regardless intensive research that confirmed the medicinal benefits of curcumin, the yellow condiment continues to intrigue more researchers to explore its activities on recently validated therapeutic targets [21–23]. Curcumin ameliorates response of cancer cells towards several cytotoxic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the cutoff threshold for considering the fold changes of proteins identified from the iTRAQ study as significantly differentiated, 2 equal amounts of 6-protein mixtures (Applied Biosystems, 4352135) were trypsin-digested and labeled with the iTRAQ reagents. 29,[50][51][52] The standard deviation of all the ratios of the labeled peptides was computed as 0.15. Thus, with the use of a 1 § 2 standard deviation formula, the ratio-change cutoff thresholds were set as 1.3 for upregulated proteins and reciprocally 0.77 for downregulated proteins.…”
Section: Resultsmentioning
confidence: 99%